Food and Social Media: You Are What You Tweet - Rousseau, Signe (Rowman & Littlefield Publishers, 2012)
Social media platforms have quickly become integral to most people’s lives, both privately and professionally. This is the first book to illuminate the trend of relying on social media in the food world. Engaging in social media is fun, but it is also rapidly becoming the platform for self-promotion and branding. This entertaining narrative offers an historical account of the major changes brought about by the Internet and also explores the polarities that underlie the challenges of adaptation, including exclusivity versus democracy, professionalism versus amateurism, and business versus pleasure. Loaded with insight into the current scene, it discusses controversies such as celebrity chefs’ tweeting wars, ethics and the accusations of plagiarizing of recipes, and etiquette concerning the practice of photographing a meal to blog about it. Food and Social Media will appeal to anyone with an interest in food and media as well as those who enjoy using any of the social media formats, including blogs, Yelp, Facebook, YouTube, Twitter, and more, to participate in a digital food community.